2005
DOI: 10.2113/gscanmin.43.5.1553
|View full text |Cite
|
Sign up to set email alerts
|

Core Mantle Chemical Issues

Abstract: Is the core's chemical isolation from the mantle complete? This is an important question for the balancing of the persistently enigmatic budgets of the highly siderophile elements and PGE, to which Fleet's work has contributed so much. On redox criteria alone, it is clear that the core and the mantle cannot be in bulk equilibrium, and therefore that there are chemical incentives for core-mantle exchange. Recent Os isotope evidence suggests that the core may indeed be leaking chemically (although some W isotope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Jeanloz (1990) suggested that chemical reactions and transport of light elements into the core could have occurred over most of the Earth's history. Subduction of oxidized ocean crust may also drive reactions by altering chemical conditions at the base of the mantle (Walker, 2005). In either case, chemical reactions could disturb the composition of the core by permitting a flux of mass between the mantle and the core.…”
Section: Chemical Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jeanloz (1990) suggested that chemical reactions and transport of light elements into the core could have occurred over most of the Earth's history. Subduction of oxidized ocean crust may also drive reactions by altering chemical conditions at the base of the mantle (Walker, 2005). In either case, chemical reactions could disturb the composition of the core by permitting a flux of mass between the mantle and the core.…”
Section: Chemical Interactionsmentioning
confidence: 99%
“…Alternatively, the excess concentration could drive back reactions at the CMB, removing excess light element and precipitating a solid 'sediment' to the base of the mantle . Walker (2005) had also discussed the possibility of electrochemical reactions at the CMB (Kavner and Walker, 2006) and reactions with oxidized oceanic crust. There is no shortage of mechanisms that can cause chemical interactions between the core and the mantle, and there are good reasons for suspecting that many of these operate within the Earth.…”
Section: Chemical Interactionsmentioning
confidence: 99%
“…Perhaps the area of most active research regarding this issue is that related to anomalous Os isotope ratios seen in some plume basalts, and thought to represent chemical exchange between the outer core and the lower mantle (Walker et al, 1995;Brandon et al, 1998;Brandon and Walker, 2005;Lassiter, 2006;Walker, 2005). The anomaly might be explained if the inner core fractionates Os from Re and Pt.…”
Section: Diffusion At Depth In Earthmentioning
confidence: 99%
“…The reaction products are thought to include iron alloys, such as FeO and FeSi, and iron-depleted silicate minerals (Knittle and Jeanloz, 1989;Goarant et al, 1992). Subduction of oxidized ocean crust may also drive reactions by continually altering chemical conditions at the base of the mantle (Walker, 2005). On the other hand, convection in the mantle exposes fresh surfaces of unreacted material Mantle Inner core Equipotential surfaces Figure 7 Schematic illustration of the heterogeneous Earth viewed on an equatorial cross section.…”
Section: Chemical Interactionsmentioning
confidence: 99%
“…Differences in redox state imply that the core and the mantle cannot be in bulk equilibrium (Walker, 2005). Differences in redox state imply that the core and the mantle cannot be in bulk equilibrium (Walker, 2005).…”
Section: Chemical Interactionsmentioning
confidence: 99%